XPS of guanidinium ionic liquids: a comparison of charge distribution in nitrogenous cations1. Issue 17 (7th May 2015) - Santos, Ana R.; Blundell, Rebecca K.; Licence, Peter
<x xml:space="preserve">Abstract</x> We report first X-ray photoelectron spectroscopy (XPS) for a range of functionalised guanidinium based systems that find application in the dissolution of biomolecules. Measured binding energies are compared to those of more common ionic liquid families containing other nitrogen based cations.